IMPORTANT FACTORS FOR FORMATION OF SOCIAL ACTIVITY SKILLS IN STUDENTS OF HIGHER EDUCATIONAL INSTITUTIONS - Tatyana Yurievna Pomytkina (Journals Park Publishing, 2022)
This article examines the role of motivation and motivation in the formation of social activity skills in students and the importance of their application in practice on a scientific basis.
Keywords: personality; humanities; educational processes